Implementation of Management Information Systems in Assessing Organizational Performance Using DeLone & McLean IS Success at BSI Bandung - Sudrajat Sudrajat; Novi Rukhviyanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In the last decade, Management Information Systems (MIS) have become an essential element in business operations in Indonesia. Management information systems have evolved from data storage tools to decision support systems essential for a dynamic business environment. Data were collected by distributing questionnaires directly to 20 Islamic Banking employee respondents. This method uses the Delone & McLean Is Success Model, which is a model for testing the success of information systems management that is seen based on 6 dimensions, namely system quality, information quality, use quality, satisfaction quality, performance effectiveness, and the last is organizational performance. The results of the study indicate that the implementation of Management Information Systems at PT Bank Syariah Indonesia (Persero) Tbk. Bandung is in the high to very high category based on the DeLone & McLean Model. User satisfaction is 86%, becoming the highest value, which indicates that the system has met employee needs and supported operational activities optimally.